2008
DOI: 10.1345/aph.1k328
|View full text |Cite
|
Sign up to set email alerts
|

Potential Influence of Antisecretory Therapy on the Development of Candida-Associated Intraabdominal Infection

Abstract: No significant difference was found in the number of patients in the antisecretory and control groups from whom peritoneal Candida was recovered. However, patients with prior abdominal surgery and those in the community with chronic PPI use may be predisposed to Candida-associated intraabdominal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 33 , 38 40 Moreover, PPI intake has been proposed as a risk factor for Candida esophagitis in immunocompetent individuals, and case-controlled studies have indicated that chronic PPI use might be a predisposing factor to Candida-associated intra-abdominal infections. 41 , 42 PPIs are widely used drugs in clinical practice, and the rate of inappropriate prescriptions without indication is high. Our data implicate that particularly in patients with PSC, a critical evaluation of the indication for PPI is necessary to avoid biliary candidiasis and further disease progression.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 38 40 Moreover, PPI intake has been proposed as a risk factor for Candida esophagitis in immunocompetent individuals, and case-controlled studies have indicated that chronic PPI use might be a predisposing factor to Candida-associated intra-abdominal infections. 41 , 42 PPIs are widely used drugs in clinical practice, and the rate of inappropriate prescriptions without indication is high. Our data implicate that particularly in patients with PSC, a critical evaluation of the indication for PPI is necessary to avoid biliary candidiasis and further disease progression.…”
Section: Discussionmentioning
confidence: 99%